Teaching Public Speaking at Kind English Course Pare-Kediri: Teaching Public Speaking at Kind English Course Pare-Kediri - sukirman muhammad; M. Labib Al Halim (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study was aimed to know the method used in Teaching Public Speaking at Kind English Course Pare-Kediri. The method used in this case was descriptive qualitative research. It means that the data gotten were described qualitatively. The researcher conducted the research in public speaking class at Kind English Course. The researcher used purposive sampling and took Public Speaking class as the participants because this class is the most wanted class. This is the only class in Kind English Course that holds the placement test in accepting the students. The class is always full in every period, and so many people say that Public Speaking class is one of the recommended classes. The researcher got the result from the observation, interview, and documentation as well as interview with the teacher that teaching learning process in the class is run well. In the teaching learning process, the teacher prepared the material well and explained the material using various methods. Subsequently, the evaluation was done every day after students performed their speech. Furthermore, the way the teacher teaches, the method used, the material and the environment become a complete package that Kind English Course offers to develop the student speaking ability.